Morphological fruit characters and nutritional food value of different jackfruit (Artocarpus heterophyllus Lam.) cultivars in Rajshahi region of Bangladesh (Bangladesh Journal of Scientific and Industrial Research, 2014)
Morphological fruit characters and nutritional food value of different jackfruit cultivars were studied during May to July 2012 to find out the superior ones in terms of the standard variables. The different cultivars of jackfruit were collected from Rajshahi, Natore, Noagoan and Chapai Nawabgonj. These cultivars showed variability in morphological fruit characters and nutritional food values. Among them the percentage of pulp (38.60-47.37%), percentage of rind (15.67-20.00%), percentage of skin (14.86-23.68%), percentage of seed (09.46-19.33%), moisture content (63.39-76.62%), TSS (18.80-27.37%), total sugar (11.84-17.01%), vitamin C content (17.82-31.55 mg/100gm) and acidity (0.037-0.075% as citric acid) were estimated. The findings show that, evaluation of these promising cultivars have identified them as superior ones. The data provide important information in improving the quality characteristics of jackfruit for plantation and processing industry. DOI: http://dx.doi.org/10.3329/bjsir.v48i4.18280 Bangladesh J. Sci. Ind. Res. 48(4), 287-292, 2013